(untitled) (Research, Society and Development, 2021)
The importance of this research is justified because it deals with a topic of great relevance for furthering the study related to the topic. The general objectives of this work are to emphasize the importance of risk classification, identifying users’ knowledge about it, in order to prevent damage to the health of patients resulting from the dissatisfaction often caused by the classification of users received during screening, in an Emergency Unit UPA service located in the municipality of Imperatriz-MA; and the specific ones: Characterize what is a health risk classification and what are the assessed risks; Knowing the users’ perception regarding the purpose of the health risk classification; Highlight the importance of screening in health care and thus improve risk classification outcomes. The methodology of this work consists of a quantitative approach. As a methodological procedure, the research will be of the descriptive type and regarding the technical procedures, it will be of the survey type research. It is exploratory as it will also be based on bibliographic research, using scientific material, doctrine, journals and websites. The results of this work were privileged the literatures that meet the risk classification, which is a work methodology linked to the area of ​​risk classification and that the key part of care is the nurse, a higher-level professional who orders , classifies, diagnoses cases that enter a particular emergency room or even an Emergency Care Unit (UPA). Where the conclusion of the survey results was reached and thus, of the 100 participants who answered the questionnaire about whether they knew the importance of screening for care, 68% answered yes, and 32% did not know the importance of screening for care . With regard to risk classification, 52% answered yes, while 48% said they did not know what the risk classification was for. Thus, from the speeches elaborated by the subjects, it was possible to perceive their perception regarding the service at the UPA São José, as shown in the graphs.